Kajian Multidimensi Keberlanjutan Perkebunan Pala Di Halmahera Tengah (Jurnal Agribisnis Indonesia, 2025)
The Indonesian nutmeg (Myristica fragrans Houtt) plantation sector, despite its significant role in the national agricultural GDP, is experiencing a decline in productivity stemming from fundamental structural issues, rather than merely technical cultivation factors (plant age, seeds, labor). Critical concerns encompass economic disincentives for farmers, who operate as price-takers, and the degradation of social sustainability, evidenced by career shifts and diminished interest among the younger generation. This study aims to assess the sustainability of smallholder nutmeg farming in Central Halmahera and to identify the sensitive factors influencing it. The method employed was Multi-Dimensional Scaling (MDS) using the Rapid Appraisal for Nutmeg (Rap-Nutmeg) approach, a modification of RAPFISH. The analysis was conducted across five sustainability dimensions—economic, social, environmental, technological, and institutional—and validated through leverage and Monte Carlo analyses. The findings indicate that, in a multidimensional perspective, nutmeg farming falls into the moderately sustainable category. The social and environmental dimensions were found to be highly sustainable, the technological dimension was moderately sustainable, while the economic dimension was less sustainable and the institutional dimension unsustainable. These results emphasize that social and environmental strengths can serve as a foundation to improve weaker dimensions, particularly economic and institutional aspects. Therefore, strengthening farmer institutions, improving access to markets and technology, and implementing sustainability-oriented policies are crucial strategies to develop nutmeg as a competitive and environmentally friendly regional commodity.